High-power lithium-ion microbatteries from imprinted 3D electrodes of sub-10 nm LiMn2O4/Li4Ti5O12 nanocrystals and a copolymer gel electrolyte. (October 2018) - Li, Wenhao; Christiansen, Troels Lindahl; Li, Cheng; Zhou, Yiliang; Fei, Huafeng; Mamakhel, Aref; Iversen, Bo B.; Watkins, James J.
Abstract: Miniaturized energy-storage components are important to self-powered microelectronics. Microbatteries based on 3D electrode architectures hold great potential to meet the demands of high-power and high energy densities. Despite the progress in microelectrode fabrication, reports of high-performance, fully integrated 3D microbatteries are still limited due to strict material requirements and more importantly, significant hierarchical processing complexities. Here, a 3D lithium-ion microbattery made from solvothermally synthesized sub-10 nm LiMn2 O4 /Li4 Ti5 O12 nanocrystals and a novel copolymer gel electrolyte is presented and is shown to possess superior capacity retention (40% at 300 C) and high-power density (855.5  μ Wcm −2 μ m −1 ) comparable to some of the best microsupercapacitors. The customized microelectrodes are fabricated by solvent-assisted imprint lithography of well-dispersed nanoparticle ink and the battery cell is integrated vertically through layer-by-layer (LBL) assembly. The fabrication strategy proposed here can be applied to a variety of electroactive materials. This work provides a combinatorial approach and highlights the synergetic effects of material synthesis, processing and device design for achieving high-performance micropower sources. Graphical abstract: fx1 Highlights: High-power, fully integrated 3D lithium-ion microbattery fabricated from imprinted microelectrodes and a nanoscale copolymer gel electrolyte. Solvothermally synthesized sub-10 nm LiMn2O4/Li4Ti5O12 nanocrystals facilitate fast ion diffusion and delicate 3D patterning. Dopamine and PEG containing copolymer gel electrolyte facilitates rapid ion transfer. First report of microbattery full cell fabrication from direct imprinting crystalline nanoparticle inks.